North American spoken English [videorecording] - Zerna, Gene (Hong-Ik Media, 1993)
A practical, intensive speech, training in relaxed settings, for anyone who wants more command of spoken English. Includes speech exercises and drills, lip and tongue articulation and points of vibration, etc.